Rebound bursts in GABAergic neurons of the thalamic reticular nucleus in postnatal mice - Wang, X; Yu, G; Hou, X; Zhou, J; Yang, B; Zhang, L (Physiological research, 2010)
Whole cell patch-clamp recordings from GABAergic cells of thalamic reticular nucleus (RTN) in thalamocortical slices made from postnatal day 6 (P6) to 10 (P10) were used to investigate the pattern of rebound bursts (RBs) triggered by an injection of hyperpolarizing current into RTN cells. The number of RBs in the RTN and the overlying Na+/K+ spikes changed in an agedependent manner. The generation of RBs depended largely on the amplitude of the after-hyperpolarizations (AHPs). RB patterns in response to hyperpolarizing current injection into relay cells were markedly different from RB patterns in RTN cells with an after-depolarization. GABAA receptor antagonist bicuculline methiodide (BMI) changed burst firing patterns, increasing the duration of RB and decreasing the amplitude of AHP in RTN cells. Furthermore, local puffs of NMDA in the presence of BMI induced RBs. K+ channel blocker 4-aminopyridine partially mimicked the effect of BMI on AHPs. The shapes of RBs were altered by a selective CaMKII inhibitor KN-62, but not by an inactive analog KN-04.
Keywords: Receptors, GABA-A; financování organizované; Animals; Thalamic Nuclei; novorozená zvířata; proteinkinasa závislá na vápníku a kalmodulinu typ 2; bikukulin; antagonisté receptorů GABA-A; receptory GABA-A; 1-(5-isochinolinsulfonyl)-2-methylpiperazin; nervový útlum; inhibitory proteinkinas; GABA; GABA antagonisté; gamma-Aminobutyric Acid; Action Potentials; GABA-A Receptor Antagonists; Animals, Newborn; Neural Inhibition; Potassium Channel Blockers; Mice; neurony; Organ Culture Techniques; GABA Antagonists; myši; Financing, Organized; orgánové kultury - kultivační techniky; Neurons; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Bicuculline; Protein Kinase Inhibitors; Mice, Inbred ICR; 4-aminopyridin; myši inbrední ICR; blokátory draslíkových kanálů; zvířata; 4-Aminopyridine; jádra thalamu; akční potenciály; 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine